The Thickening Plot: Notable Liaisons between French and English Cookbooks, 1600-1660 - Marcoux, Paula (Petits Propos Culinaires, 2025)
The author won an Award under the Sophie Coe Prize, 1998, for this essay, as explained on page 7. She holds a degree in Anthropology from Brown University, and for several years balanced her work as a field archaeologist by cooking professionally in the archaeological off-season. Since 1987 she has worked at Plimoth Plantation (a living history museum in Plymouth MA) doing research and education on how English culture, including foodways, adapted to the circumstances of New England in the 1620s. She tells us: ’Here it dawned on me that there might be such a thing as an archaeology of cooking. Lo and behold, others were already working in the field. This essay is the result of research I did in a Radcliffe Graduate Seminar instructed by Barbara K. Wheaton.’